Medial plating versus newly designed intramedullary nail with distal interlocking system for distal tibia fractures: A biomechanical study with finite element analysis - Unal, Omer Kays; Dagtas, Mirza Zafer; Najafov, Turan; Demir, Cihan; Ugutmen, Ender; Akpinar, Fuat (TURKISH JOINT DISEASES FOUNDATION, 2026)
Objectives: The aim of this study was to compare the biomechanical properties of a newly designed Tibial Intramedullary Nail-Distal Supportive Bolt Locking Screw (TIN-DSBLS) and medial anatomical plate in distal tibia fracture models using finite element analysis (FEA). Materials and methods: Twelve medium-size, fourth-generation composite tibia models were used for testing. Models were divided into two groups as plate and nail group. A standardized osteotomy was made through each model. In the plate group, osteotomized models were fixed with distal tibia medial anatomic plate. Models in nail group were fixed with new design intramedullary nail with distal Bolt screw locking. All bone models were tested by an axial loading test machine to measure the force, maximum force, fracture site displacement and Stiffness. The second step of this study was FEA of the two models. Results: The results of axial loading test results of two groups revealed that for distal tibia fracture, tibia nail which was locked with newly designed bolt screw showed superiority against plate-screw fixation about force (1597.76 +/- 85.54 vs. 830.74 +/- 146.7 N), maximum force (3617.6 vs. 1512.42 N), fracture site displacement (4.89 +/- 1 vs. 7.85 +/- 0.5 mm) and stiffness (357.88 +/- 52.6 vs. 109.67 +/- 13.6 N/mm). In FEA, maximum stress levels in implants were 1.7 time higher in nail group, bones were not exposed to higher levels of stress or deformation as in plate group. Maximum stress levels in bones of the nail group were 2.75 times lower than plate group. Total displacement in the plate group was more than two-fold compared to the nail group. Conclusion: Our study results showed that the TIN-DSBLS provides more load transfer from the nail to the cortex in tibia distal metaphyseal fractures compared to traditional nails. Taken together, it is biomechanically superior to plate-screw fixation in fractures extending up to 2.5 cm proximal to the ankle joint.
Keywords: Biomechanic analysis; distal tibia fracture; finite element analysis; osteosynthesis; FIXATION; SCREWS; STABILITY; LOCKING; NUMBER; Orthopedics; Surgery